Adaptive Timing of Motor Output in the Mouse: The Role of Movement Oscillations in Eyelid Conditioning - Chettih, Selmaan N.; McDougle, Samuel D.; Ruffolo, Luis I.; Medina, Javier F. (Frontiers in Integrative Neuroscience, 2011)
To survive, animals must learn to control their movements with millisecond-level precision, and adjust the kinematics if conditions, or task requirements, change. Here, we examine adaptive timing of motor output in mice, using a simple eyelid conditioning task. Mice were trained to blink in response to a light stimulus that was always followed by a corneal air-puff at a constant time interval. Different mice were trained with different intervals of time separating the onset of the light and the air-puff. As in previous work in other animal species, mice learned to control the speed of the blink, such that maximum eyelid closure occurred at the interval used during training. Despite this, we found that maximum eyelid speed always occurred in the first 100 ms of the movement, indicating that speed is not uniformly adjusted throughout the duration of the blink. A new analysis, specifically designed to examine the kinematics of blinks in single trials, revealed the nature of the underlying control signal: the learned blinks are made up of oscillatory eyelid movements that are time-locked to the light stimulus at the beginning of the blink, becoming desynchronized later on. Furthermore, mice learn to blink at different speeds and time the movement appropriately by adjusting the amplitude, but not the frequency of the underlying eyelid oscillation.